2018
DOI: 10.1111/cdep.12305
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequality and the Developing Brain: Spotlight on Language and Executive Function

Abstract: Robust evidence of the deleterious effects of poverty on children's academic achievement has generated considerable interest in the neural mechanisms underlying these associations. In studies of specific neurocognitive skills, researchers have found pronounced socioeconomic disparities in children's language and executive function (EF) skills. In this article, we review research linking socioeconomic factors (e.g., family income, parental education) with children's brain structure and function, focusing on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 48 publications
(67 reference statements)
2
76
0
2
Order By: Relevance
“…This pattern of results is also in line with prior structural and task-based brain imaging studies showing interactions between SES and neural variables in relation to test performance (Leonard et al, 2019;Merz, Wiltshire, et al, 2019). For example, several studies have found SES differences in lateral prefrontal and parietal activation during cognitive tasks, core nodes of the LFPN (e.g., Finn et al, 2017;Sheridan et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…This pattern of results is also in line with prior structural and task-based brain imaging studies showing interactions between SES and neural variables in relation to test performance (Leonard et al, 2019;Merz, Wiltshire, et al, 2019). For example, several studies have found SES differences in lateral prefrontal and parietal activation during cognitive tasks, core nodes of the LFPN (e.g., Finn et al, 2017;Sheridan et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Fourth, in this study, we have not included a measure of socio‐economic status. Future studies should consider that socio‐economic status may have a role in the interplay between EFs and peer acceptance/rejection, given that it is associated with both EFs and social relationships (Merz, Wiltshire, & Noble, ; Ridge, ). Fifth, we also acknowledge that although cross‐lagged panel models are widely used to examine structural relations of repeated measures constructs (Selig & Little, ), they focus on interindividual variability and are not informative with respect to intraindividual variability in the study of developmental processes (Berry & Willoughby, ).…”
Section: Discussionmentioning
confidence: 99%
“…Humans are a highly adaptable species, and one aspect of this adaptivity is adaptation of biological processes and systems, including stress response systems and epigenetic profiles to conditions of adversity in ways that affect brain function and behaviour. The adverse consequences of this adaptation has been demonstrated repeatedly in multiple programs of research (Evans & Schamberg, ; Merz, Wiltshire & Noble, ), including our own (Blair et al, ). But unless these models are accompanied with extensive and careful qualification, they can be easily interpreted as implicitly supporting deficit models of children's development through a lens that is largely individually rather than structurally and community‐focused.…”
Section: Adaptation Not Deficitmentioning
confidence: 74%